Colon-targeted engineered postbiotics nanoparticles alleviate osteoporosis through the gut-bone axis - Tingting Yu; Rushui Bai; Zeming Wang; Yuting Qin; Jingwei Wang; Yaohua Wei; Ruifang Zhao; Guangjun Nie; Bing Han (Nature Communications)
Abstract The potential for mitigating intestinal inflammation through the gut-bone axis in the treatment of osteoporosis is significant. While various gut-derived postbiotics or bacterial metabolites have been created as dietary supplements to prevent or reverse bone loss, their efficacy and safety still need improvement. Herein, a colon-targeted drug delivery system is developed using surface engineering of polyvinyl butyrate nanoparticles by shellac resin to achieve sustained release of postbiotics butyric acid at the colorectal site. These engineered postbiotics nanoparticles can effectively suppress macrophage inflammatory activation, modulate the redox balance, and regulate the composition of the gut microbiota, thereby restoring epithelial barriers, inhibiting bacterial invasion, and down-regulating pro-inflammatory responses. As a result, the remission of systemic inflammation is accompanied by a rebalancing of osteoblast and osteoclast activity, alleviating inflammatory bowel disease-related and post-menopausal bone loss. Specifically, the treatment of engineered postbiotics nanoparticles can also improve the quality and quantity of bone with restoration of deteriorative mechanical properties, which indicating a therapeutic potential on fracture prevention. This study provides valuable insights into the gut-bone axis and establishes a promising and safe therapeutic strategy for osteoporosis.